Sediment profiling of the nesting grounds of horseshoe crabs at East Peninsular Malaysia - John, Akbar; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal; Kassim, Zaleha (Canadian Center of Science and Education, 2012)
Horseshoe crabs prefer beaches with loosely packed sediment for the nesting of their eggs. In present study, Sediment profile at the observed the nesting grounds of horseshoe crabs along the east peninsular Malaysian coast were investigated. Two sampling sites (Balok and Pekan) were observed to be the nesting grounds of horseshoe crabs along the Pahang coast, east coast Malaysia. Mean sediment size analysis (ø phi) showed that during the non-monsoon and monsoon seasons, the distribution of sediment at the nesting grounds was mostly were of median sediment (1.88±0.378ø) and finer sediment (2.249±0.114ø) at Balok station respectively. Whereas, the distribution of sediment at the Pekan nesting ground was median sediment (1.073±0.388ø) at non monsoon and coarse sediment (0.641±0.075ø) at monsoon season. The nature of sediments were of moderately well sorted in both the sampling stations. There was no significant difference in sediment size or sorting value during monsoonal cycle. The results clearly showed that the sediment nature at the Balok and Pekan are still conducive for the better nesting of horseshoe crabs